Intermediaries and local knowledge in a changing political environment: complaints from Libya at the turn of the 20th century - Sievert, Henning (Die Welt des Islams, 2014)
As historiography on Ottoman Tripolitania and Benghazi focuses mainly on the Italian invasion and on the Sanūsiyya and pays little attention to Ottoman records, studies on political practice and change in that period are rare. However, the special circumstances of that remote and sparsely populated part of the empire enable us to focus on the role of intermediaries and complaints within the imperial framework. Complaints and related correspondence were crucial in the negotiation of order, both from the government’s and from the subjects’ point of view. With the 19th-century reforms, new notions of order emerged, and old notions were modified. The new mode of politics did not, however, consist of immutable prescriptions but could acquire new layers of meaning in a process of translation into the vernacular politics of the Libyan provinces and vice versa. Imperial notions of order were thus read and utilised in various ways. The key interpreters and translators in this process were intermediaries between imperial, provincial and local levels. This contribution suggests to study political communication within the imperial framework by focussing on these intermediaries.